Carborane-linked 2'-deoxyuridine 5'-O-triphosphate as building block for polymerase synthesis of carborane-modified DNA - Balintová, Jana; Simonova, Anna; Białek-Pietras, Magdalena; Olejniczak, Agnieszka; Lesnikowski, Zbigniew J; Hocek, Michal (Bioorganic & medicinal chemistry letters, 2017)
5-[(p-Carborane-2-yl)ethynyl]-2'-deoxyuridine 5'-O-triphosphate was synthesized and used as a good substrate in enzymatic construction of carborane-modified DNA or oligonucleotides containing up to 21 carborane moieties in primer extension reactions by DNA polymerases.
Keywords: DNA; Deoxyuracil Nucleotides; oligonukleotidy; Boranes; Nucleotides; DNA-dependentní DNA-polymerasy; Oligonucleotides; DNA Primers; Carboranes; polymerázová řetězová reakce; DNA polymerase; borany; Polymerase Chain Reaction; DNA-Directed DNA Polymerase; Nucleoside triphosphates; DNA primery; deoxyuracilnukleotidy